Exuberance - Kurtz, Paul (Prometheus Books, 2015)
Happiness is within everyone's grasp and is only a matter of making the right choices. Taking destiny into one's own hands and having the creative audacity to strive, seek, and meet challenges is the essence of life's drama and exaltation. Life per se has no meaning; it only presents opportunity to be seized and acted upon, thus paving the way for personal achievement and the full life. Paul Kurtz, in -- From the Trade Paperback edition.